Butchering activity is the main risk factor for hepatitis E virus (Paslahepevirus balayani) infection in southwestern Nigeria: a prospective cohort study - Oluremi, Adeolu S.; Casares-Jimenez, Maria; Opaleye, Oluyinka O.; Caballero-Gomez, Javier; Ogbolu, David Olusoga; Lopez-Lopez, Pedro; Corona-Mata, Diana; Rivero-Juarez, Antonio; Rivero, Antonio (Frontiers in Microbiology, 2023)
Introduction: Paslahepevirus balayani (Hepatitis E virus; HEV) is an emerging virus that poses as a public health threat. The virus is now reported to be the leading cause of acute viral hepatitis, with a unique impact on African settings. Our aim was to evaluate the prevalence and risk factors for HEV infection in three cohorts (animal handlers, villagers, and students). Methods: A prospective cross-sectional study was carried out on a total of 752 subjects from southwestern Nigeria. In all individuals, anti-HEV IgG and anti-HEV IgM antibodies were evaluated by using ELISA (confirming positive results via immunoblotting), and serum viral RNA was evaluated by using two RT-PCR assays. Results: The overall seroprevalence of HEV IgG and HEV IgM was 14.9% (95% CI: 12.5-17.6%) and 1.3% (95% CI: 0.7-2.5%), respectively. We observed the highest seroprevalence among animal contact individuals, with butchers being the population with the highest HEV IgG seroprevalence (31.1%). Similarly, HEV IgM was higher in the animal contact group (2.2%) than in the non-animal contact cohort (0%). Discussions: Viral RNA was not detected in any of the samples. Butchering was significantly associated with higher HEV prevalence. Although all efforts to prevent HEV in Africa have focused on the chlorination of water, our study suggests that most new infections could currently be linked to animal manipulation. Therefore, education and guidelines must be provided in southwest Nigeria to ensure that animal handling and processing methods are safe.